Muscular Weakness and Loss of Motor Skills in Patients with Cerebral Palsy - Olga A. Klochkova; Alexey L. Kurenkov (Вопросы современной педиатрии, 2020)
Various aspects of muscle strength decrease and loss of motor skills in patients with cerebral palsy (CP) are considered in this review. Pathophysiological mechanisms caused by primary damage and reorganization of central nervous system (CNS), structural-functional changes of muscle tissue, biomechanical disbalance are described. Changes at patients with CP equate with sarcopenia (physiological process of muscle strength and function loss in elderly patients). It has been shown that patients with cerebral palsy have such phenomenon as «early aging» of musculo-skeletal system. Potential approaches for prevention of sarcopenia in children and adults with cerebral palsy are discussed. Understanding of the described mechanisms of primary and age-related changes in muscle tissue in early CNS injuries is necessary to plan the activities of daily living for patients, choose the correct rehabilitation tactics, minimize adverse therapeutic effects, and reasonable management of comorbid conditions.